What Affects Users to Click on Display Ads on Social Media? The Roles of Message Values, Involvement, and Security. Issue 2 (3rd April 2017) - Mao, En; Zhang, Jing
ABSTRACT: This project represents one of the few efforts in studying the effectiveness of social media advertising (ads). Specifically, the effects of three major communication components—message, channel/media, and receiver/audience—on ad clicks are examined. The message component includes perceived informativeness, entertainment, and intrusiveness of the ad; the media component focuses on social media security and the audience component focuses on their involvement. The effects of ad clicks on product evaluations and then on intentions to spread positive word-of-mouth are also investigated. A research model is developed and tested with online-survey data from 572 social media users. The contributions, practical implications, and future research directions are discussed in the context of social media.